The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1097/scs.0000000000002055
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Maxillofacial Trauma Among Alcohol and Drug Users

Abstract: The aim of the current study was to identify and compare the characteristics of maxillofacial trauma in alcohol and drug users with those of nonusers. A retrospective study was conducted using the medical records of patients treated for facial trauma between April 1999 and March 2012 at the Maxillofacial Surgery Division of the Piracicaba Dental School. The data were analyzed by descriptive analysis, binary logistic regression, and correlational analysis using SPSS 18.0 software. The results were considered re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 17 publications
2
20
0
Order By: Relevance
“…911 One study found that mandible fractures were primarily caused by interpersonal violence in drug and alcohol users. 12 Our results are not only consistent with these previous general epidemiologic studies on facial trauma but also novel in demonstrating that homeless patients are at much higher risk for being assaulted and suffering mandible fractures.…”
Section: Discussionsupporting
confidence: 92%
“…911 One study found that mandible fractures were primarily caused by interpersonal violence in drug and alcohol users. 12 Our results are not only consistent with these previous general epidemiologic studies on facial trauma but also novel in demonstrating that homeless patients are at much higher risk for being assaulted and suffering mandible fractures.…”
Section: Discussionsupporting
confidence: 92%
“…However, the particular increases of January and September could involve other more complex components as they correspond to dates of national and international celebration (national holidays and new year). These characteristics have been described as a trigger for acts of violence (intentional injuries) (3,8,24) and road traffic crashes (unintentional) (11) where mediators such as alcohol and drugs play an enhancing role (3,8,17,24,25). Unfortunately, the detail of this information, as stated in other studies of a similar nature, is not well documented in the emergency registers (24), a fact that was repeated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A patient suspect of having a combined trauma should, therefore, always be checked by specialists of both disciplines, with available neurosurgical consultation as soon as possible. This can be a challenge due to the known large proportion of intoxicated patients [13][14][15][16][17][18][19].…”
Section: Brain Trauma In Combined Cmf-and Ot-patientsmentioning
confidence: 99%